2021
DOI: 10.1038/s41388-021-02054-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals distinct tumor microenvironmental patterns in lung adenocarcinoma

Abstract: Recent developments in immuno-oncology demonstrate that not only cancer cells, but also the tumor microenvironment can guide precision medicine. A comprehensive and in-depth characterization of the tumor microenvironment is challenging since its cell populations are diverse and can be important even if scarce. To identify clinically relevant microenvironmental and cancer features, we applied single-cell RNA sequencing to ten human lung adenocarcinomas and ten normal control tissues. Our analyses revealed heter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 77 publications
(86 reference statements)
11
89
0
Order By: Relevance
“…It suggests that TAMs can promote lung cancer progression through inhibiting tumor immunity and promoting of tumor growth and invasion. Among the subtypes of TAMs, M2 macrophages were found high expression of SELENOP, whereas M1 macrophages expressed high levels of pro-inflammatory chemokines, such as CXCL9 and CXCL10, pro-inflammatory cytokine IL1B, and M1 macrophages were also found to be associated with other myeloid cell types such as plasmacytoid DCs in LUAD via scRNA-seq ( 95 ).…”
Section: Phenotypic Molding Of Stromal Cells In the Lung Cancer Tme Under Scrna-seq Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…It suggests that TAMs can promote lung cancer progression through inhibiting tumor immunity and promoting of tumor growth and invasion. Among the subtypes of TAMs, M2 macrophages were found high expression of SELENOP, whereas M1 macrophages expressed high levels of pro-inflammatory chemokines, such as CXCL9 and CXCL10, pro-inflammatory cytokine IL1B, and M1 macrophages were also found to be associated with other myeloid cell types such as plasmacytoid DCs in LUAD via scRNA-seq ( 95 ).…”
Section: Phenotypic Molding Of Stromal Cells In the Lung Cancer Tme Under Scrna-seq Analysismentioning
confidence: 99%
“…The cluster of fibroblasts was found to be divided into seven known cell types by scRNA-seq in NSCLC ( 43 , 54 ), with COL13A1 + and COL14A1 + fibroblasts being the major fibroblast types in early NSCLC tissues ( 43 ). Moreover, myofibroblasts were found to replace fibroblasts in the TME ( 43 , 95 ), which may promote extensive tissue reconstruction ( 114 ), angiogenesis ( 115 ), and tumor progression ( 116 ). Myofibroblasts were characterized by expression of both fibroblastic marker genes, such as PDGFRA and LUM, and smooth muscle marker genes, such as MYLK and ACTA2 ( 95 ).…”
Section: Phenotypic Molding Of Stromal Cells In the Lung Cancer Tme Under Scrna-seq Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Lambrechts et al identified some heterogeneous sub-subpopulations in stromal cells and the transcription factors that regulate their heterogeneity in the early LUAD patients by scRNA-seq (43). ScRNA-seq analysis of 10 normal lung tissues and 10 fresh LUAD tissues found that the TME was composed of cancer-associated myofibroblasts, exhausted CD8 + T cells, proinflammatory monocyte-derived macrophages, plasmacytoid dendritic cells, myeloid dendritic cells, anti-inflammatory monocyte-derived macrophages, normal-like myofibroblasts, NK cells, and conventional T cells (69). Multi-region of five early-stage LUADs and 14 multi-region normal lung tissues found that the Treg + cells are increased in normal tissues with proximity to LUAD and the signatures and fractions of cytotoxic CD8+ T cells, antigen-presenting macrophages, and inflammatory dendritic cells were decreased (37).…”
Section: Single-cell Rna Sequencing In the Early Stage Of Lung Cancermentioning
confidence: 99%